Traumatic Amputation of the Thumb at the Proximal Phalanx: A Successful Reconstruction with Gillies’ Technique and Reverse Radial Forearm Flap: A Case Report - Crisologo, Cristine; Gabriel, Giselle; Sibonga, Raymar (Philippine Journal of Orthopaedics, 2025)
This case report describes a successful thumb reconstruction using a Gillies’ lengthening procedure and a reverse radial forearm flap in a 31-year-old man who suffered a traumatic thumb amputation at the level of the proximal phalanx with approximately 0.5 cm of bony stump. An iliac crest bone graft lengthened the thumb, and the radial forearm flap provided sensate coverage. Postoperatively, the flap showed excellent viability, and the reconstructed thumb achieved near-contralateral length, improving hand function.